(untitled) (Research, Society and Development, 2022)
Brazil has registered a reduction over the years in the rates referring to maternal and neonatal mortality, this drop in numbers is mainly due to the reduction in mortality from obstetric causes, and is also attributed to the development of actions by health services aimed at health care of the woman. Prenatal care is one of the strategies that provides a set of practices that seek to reduce undesirable events during pregnancy, labor and the puerperium. This study aims to analyze the quality of prenatal care provided to pregnant women assisted by the Unified Health System in the year 2021, in the municipality of Cascavel-PR, according to the criteria of the Program for Humanization of Prenatal and Birth (PHPN) . This is a prospective, quantitative and observational research resulting from the analysis of 97 medical records of pregnant women in Cascavel-PR. For statistical analysis, Fisher’s test was used, with a significance level of p <0.01. This study observed that pregnant women who started prenatal care in the first trimester were 17.97 times more likely to have the minimum number of six consultations, with six consultations being considered as a parameter to analyze the quality of prenatal care. In this study, most pregnant women had six consultations during prenatal care, providing the municipality with adequate prenatal care in most cases. According to this data, it is important to start an early prenatal care as a way to prevent and detect pathologies that may compromise the health of the pregnant woman and the fetus.